Beat plunder charge by subtracting P1,000 from P50-M threshold - Uy, Jocelyn R. (2017)
Senators were stunned when they were informed that the bribe money supposedly intended for the release of more than 1,300 illegal Chinese workers arrested during a raid on Lam's casino in Pampanga province in November last year was P1,000 short of a plunder case.
Keywords: Plunder; Lam, Jack